"Yes, we can!": Perceptions of collective efficacy sources in volleyball - Fransen, K.; Vanbeselaere, N.; Exadaktylos, V.; vande Broek, G.; de Cuyper, B.; Berckmans, D.; Ceux, T.; de Backer, M.; Boen, F. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
`We have to believe that we can make it as a team!` Coaches, players and other sport enthusiasts routinely talk about the importance of team confidence. Psychologists refer to this concept as collective efficacy, defined as `a group`s shared confidence that they will successfully achieve their goal`. Previous research findings revealed that teams with a strong sense of collective efficacy set more challenging goals, exert more effort, and are ultimately more likely to succeed. Nevertheless, little is known about the sources contributing to the development of collective efficacy. Therefore, in this study we examined which behaviours and events are perceived as sources of collective efficacy beliefs in volleyball. Study 1 In Study 1, volleyball coaches from the highest volleyball leagues (n=33) in Belgium indicated the most important sources of collective efficacy. This list was then adapted based on the literature and on feedback given by an expert focus group, resulting in a 40-item questionnaire. Study 2 In Study 2, coaches and players from all levels of volleyball in Belgium (n=2,365) rated each of these sources on their predictive value for collective efficacy. A principal component analysis revealed that the 40 sources could be divided into eight internally consistent components. Positive supportive communication (e.g. enthusiasm after making a point) was identified as the component most predictive for positive collective efficacy beliefs. The component referring to negative emotional reactions of players (e.g. discouraged body language) was most predictive for negative efficacy beliefs. Discussion: Previous research has focused on sources of collective efficacy that take place before the game. Within that perspective, past performance was found to be the strongest source of efficacy beliefs. By contrast, in the present study, positive supportive communication, including sources during the game, was rated even more predictive for collective efficacy. Until now, collective efficacy has never been measured during the game. One of the reasons for this research lacuna is the fact that in most team sports it is not possible to interrupt a player repeatedly during a game to measure his or her collective efficacy beliefs. Observational data might provide a viable alternative for these self-report measures. It is therefore noteworthy that in the present study the sources that were most predictive for positive collective efficacy as well as those most predictive for negative collective efficacy are clearly observable behaviours during the game. These sources may thus offer a starting point for the design of a continuous measure of players` collective efficacy beliefs through observation.